2007
DOI: 10.1080/01443610701194978
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of experimental and clinical studies of sildenafil citrate for intrauterine growth restriction and pre-term labour

Abstract: Sildenafil could be an alternative in the treatment of intrauterine growth retardation (IUGR) and premature delivery. In order to systematically review the reproductive-related effects of sildenafil, a search was made on PubMed and the Science Citation Index for studies evaluating the effects of sildenafil on uterine vessels or myometrium either in vitro or in experimental animal models as well as for any clinical trial or case reporting the outcome of pregnant women treated with sildenafil. The information wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 25 publications
2
54
1
1
Order By: Relevance
“…Sildenafil citrate is increasingly used for pulmonary hypertension in pregnancy, and is also emerging as a potential candidate for the treatment of intrauterine growth retardation and for premature labour [14]. Sildenafil has also been proposed as a potential therapeutic strategy to maintain placental function in pre-eclampsia [15].…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil citrate is increasingly used for pulmonary hypertension in pregnancy, and is also emerging as a potential candidate for the treatment of intrauterine growth retardation and for premature labour [14]. Sildenafil has also been proposed as a potential therapeutic strategy to maintain placental function in pre-eclampsia [15].…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence on the efficacy of sildenafil in intrauterine growth retardation, but no detrimental effects were found [107] There is also conflicting evidence about sildenafil in sheep models: one study reported hypoxia, hypotension, and tachycardia in animals with induced IUGR and in control fetuses [116]; another study reported dose-related increases in fetal weight in both control and nutrient-restricted ewes, and increased delivery of amino acids and polyamines to IUGR fetuses [117] 12.2.2 Conception and preservation of pregnancy Intravaginal sildenafil (also at 25 mg four times daily) has been employed in cases of recurrent miscarriage, which has been linked to various factors including NO-mediated release of tumor necrosis factor-a (TNF-a) from natural killer (NK) cells.…”
Section: Conditionmentioning
confidence: 89%
“…Data on the safety of this experimental use are limited, but no adverse effects have been reported from preclinical models or human case reports [107].…”
Section: Disorders Of Conception and Pregnancymentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, sildenafil, 1-[4-ethoxy-3-(6,7-dihydro-1-methyl-7oxo-3-propyl-1H-pyrazolo [4,3-d]pyrimidin-5-yl)phenylsulfonyl]-4-methylpiperazine, a type 5-specific phosphodiesterase (PDE) inhibitor, has been reported to improve uterine blood flow in women following intravaginal (IVG) administration 1,4,[12][13][14][15] . This increased blood flow has lead to estrogen-induced proliferation of the endometrial lining in patients with poor endometrial development resulting in successful pregnancy 4,13 .…”
Section: Introductionmentioning
confidence: 99%